A new kind of H-acid monoazo-anthraquinone reactive dyes with surprising colour. (December 2015) - Shan, Bin; Tong, Xing; Xiong, Wei; Qiu, Wenzhu; Tang, Bingtao; Lu, Rongwen; Ma, Wei; Luo, Yi; Zhang, Shufen
Abstract: A new kind of reactive dyes containing both monoazo and anthraquinone chromophores was obtained by using 1, 4-bis((4-aminophenyl)amino)anthrancene- 9, 10-dione as diazo component and 1-amino-8-naphthol-3, 6-disulfonicacid (H-acid) derivatives as coupling components. The dyes were characterized by UV–Vis, IR, MS, 1 H NMR and 13 C NMR. The results showed that the maximum absorption wavelengths of the dyes were all about 590 nm, which indicated that they were a kind of blue dyes. 1 H NMR and 13 C NMR results revealed that there were two kinds of tautomerisms in dye structure and a new conjugated system formed between the anthraquinone ring and the phenyl azo linkage. Density functional theory (DFT) calculations also proved the formation of the new larger conjugated system from which the blue colour was generated. The fixations of the dyes on cotton were over 88% and the light fastness reached 5 grade. Graphical abstract: Highlights: A new kind of blue H-acid monoazo-anthraquinone reactive dyes was obtained. New conjugated system formed between anthraquinone ring and phenyl azo linkage. This kind of dyes had high fixation on cotton and high light fastness.